Is a value of over 200 mg/dL in the oral glucose tolerance test, a marker of severity in patients with gestational diabetes mellitus?. (21st March 2013) - Atia, H. C.; Koren, Y.; Weintraub, A. Y.; Novack, L.; Sheiner, E.
Abstract: Objective : To determine whether blood glucose values of over 200 mg/dL in the oral glucose tolerance test (OGTT) are associated with pregnancy complications and adverse perinatal outcomes in patients with gestational diabetes mellitus (GDM). Methods : A retrospective cohort study was performed comparing patients with GDM A1 (diet controlled) that had at least one value of 200 mg/dL or higher in the OGTT, to those who did not. Patients were treated at the diabetes day care clinic of a tertiary medical center between the years 1999 and 2010. Data were available from the computerized perinatal databases. Results : During the study period, 778 women with GDM were treated at the diabetes day care clinic. Of these, 162 had at least one test value of 200 mg/dL or greater. No significant differences regarding maternal and perinatal complications, such as polyhydramnios, macrosomia (birth-weight above 4 kg), shoulder dystocia, low Apgar scores at 5 min (<7) and cesarean section were noted between the groups. Conclusions : A value of 200 mg/dL or more in the OGTT is not an indicator of perinatal complications.